The mitten ebook - Brett, Jan (2014)
When Nicki drops his white mitten in the snow, he goes on without realizing that it is missing. One by one, woodland animals find it and crawl in; first, a curious mole, then a rabbit, a badger and others, each one larger than the last. Finally, a big brown bear is followed in by a tiny brown mouse and what happens next makes for a wonderfully funny climax. As the story of the animals in the mitten unfolds, the reader can see Nicki in the boarders of each page, walking through the woods unaware of what is going on. Once again Jan Brett has created a dramatic and beautiful picture book in her distinctive style. She brings the animals to life with warmth and humor, and her illustrations are full of visual delights and details faithful to the Ukrainian tradition from which the story comes.